Developing and Promoting a Nuclear Security Curriculum at Amity University, India: Beginnings, Successes and Challenges - Ms. Kawalpreet Kalra; Ms. Archana Yadav; Dr. Alpana Goel (International Journal of Nuclear Security, 2016)
Amity University is one of India’s leading research- and innovation-driven private universities. The Amity Institute of Nuclear Science and Technology (AINST), established in 2009, contribute to Amity’s mission to promote national development through philanthropy, education and research. Very recently, courses related to nuclear security and security culture have been added to the existing AINST curriculum. The purpose of introducing this course was to enhance the understanding of technical, policy, and regulatory challenges associated with nuclear security and to create a nuclear security culture among relevant local institutions. This paper describes the process involved in establishing nuclear security as an elective course in the Engineering and Technology Domain for undergraduate-level and postgraduate-level engineering students at the Institute, discusses both challenges faced in these early stages as well as achievements and successes, and outlines future plans for the program.
Keywords: Education; curriculum; nuclear security culture; India